Water-soluble withaferin A polymer prodrugs via a drug-functionalized RAFT CTA approach. (January 2019) - Van Herck, Simon; Hassannia, Behrouz; Louage, Benoit; Pita Compostizo, Raquel; De Coen, Ruben; Vanden Berghe, Wim; Vanden Berghe, Tom; De Geest, Bruno G.
Graphical abstract: Highlights: Solubility of the anti-cancer drug withaferin A is dramatically improved by polymer-conjugation. Grafting-from chain transfer agent is a powerful route to well-defined polymer-drug conjugates. Withaferin A-polymer conjugates are polymeric pro-drugs. Abstract: To cope with the poor aqueous solubility of withaferin A, a broad-spectrum anti-cancer agent effective against therapy-resistant cancers, a polymer-drug conjugate was synthesized via a grafting-from-drug approach. Modification of withaferin A at the C27-OH with a chain transfer agent (CTA) for reversible addition-fragmentation chain transfer (RAFT) polymerization through a degradable ester bond was achieved with excellent control on the regioselectivity via a PFP-ester transesterification route. Subsequent RAFT polymerization with the hydrophilic N, N-dimethylacrylamide yielded a fully water-soluble conjugate. A decreased cytotoxicity in vitro indicated that withaferin A exists as a prodrug in the conjugate form and requires hydrolysis of the ester to regain its activity.